The bees of Early Eocene Cambay amber (Hymenoptera: Apidae) - Engel, Michael S.; Ortega-Blanco, Jaime; Nascimbene, Paul C.; Singh, Hukam (Journal of Melittology, 2013)
The fauna of bees known from Early Eocene (Ypresian) Cambay amber are reviewed.  Presently only three species have been recovered, all from among the corbiculate Apinae and representing the extinct tribes Electrapini and Melikertini, and all from genera known from the slightly younger middle Eocene Baltic amber.  A single, poorly-preserved and fragmentary female of an unidentifiable species of Protobombus Cockerell is recorded.  Two new species of the genus Melikertes Engel are documented, one representing a new subgenus, Paramelikertes Engel & Ortega-Blanco, as is a third, fragmentary melikertine of uncertain identity.  The new species are Melikertes (Paramelikertes) gujaratensis Engel & Ortega-Blanco, new species, and M. (Melikertes) kamboja Engel & Ortega-Blanco, new species.